Analysis and Development of Village Office Administration Management Using Extreme Programming Method - Denny Jean Cross Sihombing (SEAN Institute, 2023)
This research aims to analyze and develop village administration management using Extreme Programming (XP) method. Village administration is crucial in delivering public services, managing local resources, and supporting sustainable regional development. The prominent challenges village administration faces include system limitations, the need for integration between sections, and technological barriers. In the context of software development for village administration, this research applies the XP method, which emphasizes intensive collaboration, adaptability to changing policies or needs, and continuous testing. The research steps involved comprehensive data collection, application development with prototype release, intensive user collaboration, and continuous improvement iterations. The results showed that the village administration application developed using the XP method could provide an adaptive solution to the dynamics of village administration. Users responded positively to the user interface and ease of use of the application. The dynamic features implemented responded to changes in village policies, while users rated the application's adaptability highly. With a user satisfaction rate of 90%, effective handling of technical issues at 95%, and positive performance stabilization results, the application is considered ready for full rollout.